AW-AD-6: PREVALENCE OF VALIDATED BLOOD PRESSURE MEASURING DEVICES BEING SOLD BY AMAZON: 12-MONTH PROSPECTIVE ANALYSIS ACROSS 10 COUNTRIES. (January 2023) - Picone, Dean S; Bui, Tan; Chapman, Niamh; Schultz, Martin G; Delles, Christian; Olsen, Michael Hecht; Schutte, Aletta E; Stergiou, George; Padwal, Raj; Whelton, Paul K; Sharman, James E
Abstract : Objective: The online purchase of automated blood pressure (BP) devices is a multibillion-dollar industry, but most BP devices available for online purchase have not passed adequate clinical validation testing. This study aimed to determine the extent to which BP devices available in best-selling lists of the e-commerce business Amazon were properly validated for accuracy, as well as their cost and ratings. Design and method: The 100 best-selling automated (upper arm and wrist) cuff BP devices sold by Amazon in 10 countries located in Europe, Asia-Pacific, North and South America were recorded at seven time points during a 12-month period of observation. Results: 81% of the 100 best-selling BP devices had not undergone adequate clinical validation (interquartile range [IQR] 74 to 90, averaged across all countries and time points) and this percentage was highly consistent within each country across the measurement period. The highest percentages of properly validated upper-arm BP devices being sold were 35% in Germany and 31% in Canada, whereas the lowest percentages were 3% in India and 5% in Australia. Non-validated upper-arm cuff BP devices were cheaper than clinically validated devices (median, IQR: 32.0 USD (26.0 to 43.9) versus 67.2 USD, (42.7 to 89.7)). Non-validated upper-arm cuff BP devices received fewer total numbers of consumer ratings than clinically validated devices (median, IQR: 210, 44 to 770 versus 651, 95 to 2962) despite near identical consumer ratings out of five stars (median, IQR: 4.5, 4.2 to 4.6 versus 4.5, 4.3 to 4.7). Similar patterns were observed for wrist-cuff BP devices. None of the wrist-cuff devices being sold in the US were clinically validated. Conclusions: Four out of five automated BP devices within the 100 best-selling lists of Amazon had not passed adequate clinical validation testing for BP measurement accuracy and precision. People should not buy a BP device online unless they can be certain it has passed adequate clinical validation testing.